PERBANDINGAN EFEKTIVITAS TERAPI DAN BIAYA FILGRASTIM DAN LENOGRASTIM PADA PASIEN KANKER KOLOREKTAL DENGAN REGIMEN KEMOTERAPI FOLFOX - Pratama, Jainuri Erik; Ramadhan, Viren; Saharuddin; Pahlavi, Ridlo (Jurnal Ilmiah Farmasi, 2024)
Background: Granulocyte colony-stimulating factor (GCSF) is a primary regulator of the granulopoiesis process, which mobilizes stem cells from the bone marrow to the blood vessels. Filgrastim and lenograstim are the types of GCSF that have been widely used. Objective: This research aims to study the comparative therapeutic outcomes and cost-effectiveness of filgrastim and lenograstim therapies in colorectal cancer patients undergoing chemotherapy with the FOLFOX regimen.Method: This research was conducted at the pharmacy installation of the Dr. Kariadi Central General Hospital (RSUP Dr. Kariadi) from December 2023 to January 2024. It is observational research with a retrospective pre-posttest cohort study design that evaluates the comparative effectiveness and costs of filgrastim and lenograstim therapies in patients with neutropenia based on an increase in white blood cells (WBC) and absolute neutrophil count (ANC) scores of patients. The data was analyzed using the unpaired comparative analysis method and using the cost-effectiveness analysis (CEA) method to determine the cost-effectiveness. The observations were carried out twice, before and after administering the GCSF therapy. The samples consisted of 25 patients divided into two treatment groups. Results: The average scores of WBC and ANC levels in 15 patients who received filgrastim therapy were 2000 cells/mm3 and 666 cells/mm3. At the same time, the WBC and ANC levels in 10 patients who received lenograstim therapy were 1980 cells/mm3 and 449 cells/mm3. After administering the GCSF therapy, there was a significant increase in WBC and ANC levels (p<0.05) in each group. Still, there was no significant difference in the increase in WBC and ANC between the groups receiving filgrastim and lenograstim (p>0.05). The CEA analysis results showed that an increase of 1 cell/ml of WBC score cost Rp24.2 for filgrastim and Rp347 for lenograstim. In contrast, an increase of 1 cell/ml of ANC score cost Rp111.8 for filgrastim and Rp1572.5 for lenograstim.Conclusion: This research concludes that filgrastim is as effective as lenograstim, yet filgrastim is considered more cost-effective than lenograstim.